2019
DOI: 10.1002/widm.1333
|View full text |Cite
|
Sign up to set email alerts
|

Sentiment analysis for mining texts and social networks data: Methods and tools

Abstract: Social networks (SNs) represent an established environment in which users share daily emotions and opinions. Therefore, they have become an essential source of big data related to sentiment/opinion sphere. Sentiment analysis (SA) aims to extract sentiments, emotions or opinions from texts, made available by different data sources like SNs. This review presents a depth study relative to the methods and the main tools for SA. The analysis was performed by defining four criteria and several variables to compare 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 70 publications
0
47
0
2
Order By: Relevance
“…These suggestions are regarded the phone that was launched by Microsoft. Zucco et al [14] did not define the suggestions in their work; rather, they reported the objectives of the collection of suggestions, which was to progress and improve the quality and functionality of the product, organization, and service. The authors in [25] delivered an algorithm-"GloVE"-to train word embedding to the additional algorithms that highly perform on several benchmark tasks and datasets.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…These suggestions are regarded the phone that was launched by Microsoft. Zucco et al [14] did not define the suggestions in their work; rather, they reported the objectives of the collection of suggestions, which was to progress and improve the quality and functionality of the product, organization, and service. The authors in [25] delivered an algorithm-"GloVE"-to train word embedding to the additional algorithms that highly perform on several benchmark tasks and datasets.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, several challenges in suggestion mining approaches relate to analyzing the sentiments of the sentence, identifying the relationship between suggestions, and selecting annotators for supervised and unsupervised learning [14]. Suggestion mining is a recent research area, and thus, studies on extracting suggestions involving different classifiers and algorithms are relatively limited [15].…”
Section: Introductionmentioning
confidence: 99%
“…The full list of CoreNLP wrappers can be found in its website. 8 The survey in [51] introduces 24 utilities for sentiment analysis-9 of these tools have an API for common programming languages. However, several of these utilities are paid, but most of them provide free licenses for a limited period.…”
Section: Pythonmentioning
confidence: 99%
“…In 1872, Darwin attempted to explain the link between emotions and evolution. Following that, cognitive scientists [6] discovered that emotions are a product of other brain system processes. With development technology, emotional analysis was field of information technology research, also [20] performs the soil corpus transfer learning with better results.…”
Section: Related Workmentioning
confidence: 99%